Functional whole-brain mechanisms underlying effects of tDCS on athletic performance of male rowing athletes revealed by resting-state fMRI - Ma, Ming; Xu, Yan; Xiang, Ziliang; Yang, Xi; Guo, Jianye; Zhao, Yong; Hou, Zhenghua; Feng, Yuxu; Chen, Jianhuai; Yuan, Yonggui (Frontiers in Psychology, 2022)
Introduction: Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique that applied to modulate brain activity and enhance motor recovery. However, the neurobiological substrates underlying the effects of tDCS on brain function remain poorly understood. This study aimed to investigate the central mechanisms of tDCS on improving the athletic performance of male rowing athletes. Methods: Twelve right-handed male professional rowing athletes received tDCS over the left primary motor cortex while undergoing regular training. The resting-state functional magnetic resonance imaging (rs-fMRI) data were acquired before and after tDCS. Measures of amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) were calculated and compared between baseline and follow-up, as well as topological measures including global and local efficiency of functional brain networks constructed by graph theoretical analysis. Results: Male rowing athletes showed increased isokinetic muscle strength of the left knee and left shoulder after tDCS. Increased ALFF values were found in the right precentral gyrus of male rowing athletes after tDCS when compared with those before tDCS. In addition, male rowing athletes showed increased ReHo values in the left paracentral lobule following tDCS. Moreover, increased nodal global efficiency was identified in the left inferior frontal gyrus (opercular part) of male rowing athletes after tDCS. Conclusion: The findings suggested that simultaneous tDCS-induced excitation over the primary motor cortex might potentially improve the overall athletic performance in male rowing athletes through the right precentral gyrus and left paracentral lobule, as well as left inferior frontal gyrus.